THORACIC SPINE CANAL STENOSIS WITH CAUDA EQUINE SYNDROME: CASE REPORT - Primadenny Ariesa Airlangga; Arifin Arifin (Journal Orthopaedi and Traumatology Surabaya, 2019)
Background: Cases of thoracic stenosis with cauda equina syndrome are rare. The thoracal canal is relatively narrow compared with cervical and lumbar, so the less pressure on the lower thoracal region is the thoracic vertebral height 11 which is the initial release of the cauda equine nerve root can cause complaints of cauda equina syndrome.Case: A 50-year-old male presented pain in both legs for 3 years, accompanied by weakness in the legs, numbness in the buttocks, and erectile dysfunction. Thoracal MRI examination shows severe spinal stenosis at 11th-12th thoracal vertebra with ligamentum flavum hypertrophy. Second patient, a 70-year-old man complained of weak legs since 1 week, accompanied by low back pain, numbness in the buttocks, and difficulty defecating. Thoracal MRI examination shows severe spinal stenosis in the 10th-11th thoracal vertebra. Both patients immediately underwent selective decompression surgery, laminotomy, and flavectomy at thoracal level showed satisfactory results based on improvement in clinical symptoms.Discussion: Leg weakness, hypoesthesia in the buttocks and pubic area, erectile dysfunction is the cauda equina syndrome. The exit of the first cauda equine nerve can be placed at 11th thoracic vertebra, so the presence of stenosis at that level and bellow can cause symptoms of the cauda equina syndrome. MRI examination is needed to ensure that there is severe spinal stenosis at the level of the thoracal-lumbar spine, according to the level of neurological disorders. The surgery of decompression is immediately carried out in the case of cauda equina syndrome because it is an emergency state.Conclusion. In cases with complaints of the cauda equina syndrome, thoracic stenosis can be the cause due to stenosis of the lower thoracic region which is the initial root of the cauda equina nerve. Confirm accurate diagnosis is with MRI.